Hybrid compton-PET imaging for ion-range verification: a preclinical study for proton, helium, and carbon therapy at HIT - Balibrea-Correa, Javier; Lerendegui-Marco, Jorge; Ladarescu, Ion; Morell, Sergio; Guerrero, Carlos; Rodríguez-González, Teresa; Jiménez-Ramos, Maria del Carmen; Quesada, Jose Manuel; Bauer, Julia; Brons, Stephan; Domingo-Pardo, César (The European physical journal. Plus, 2025)
Enhanced-accuracy ion-range verification in real time shall enable a significant step forward in the use of therapeutic ion beams. Positron-emission tomography (PET) and prompt-gamma imaging (PGI) are two of the most promising and researched methodologies, both of them with their own advantages and challenges. Thus far, both of them have been explored for ion-range verification in an independent way. However, the simultaneous combination of PET and PGI within the same imaging framework may open-up the possibility to exploit more efficiently all radiative emissions excited in the tissue by the ion beam. Here, we report on the first preclinical implementation of an hybrid PET-PGI imaging system, hereby exploring its performance over several ion beam species (H, He and C), energies (55-275 MeV) and intensities ($$10^7$$-$$10^9$$ions/spot), which are representative of clinical conditions. The measurements were carried out using the pencil-beam scanning technique at the synchrotron accelerator of the heavy ion therapy center in Heidelberg utilizing an array of four Compton cameras in a twofold front-to-front configuration. The results demonstrate that the hybrid PET-PGI technique can be well suited for relatively low energies (55-155 MeV) and beams of protons. On the other hand, for heavier beams of helium and carbon ions at higher energies (155-275 MeV), range monitoring becomes more challenging owing to large backgrounds from additional nuclear processes. The experimental results are well understood on the basis of realistic Monte Carlo calculations, which show a satisfactory agreement with the measured data. This work can guide further upgrades of the hybrid PET-PGI system toward a clinical implementation of this innovative technique.
Gesehen am 26.01.2026